2021
DOI: 10.1007/s40291-020-00510-6
|View full text |Cite
|
Sign up to set email alerts
|

Current and Emerging Clinical Treatment in Mitochondrial Disease

Abstract: Primary mitochondrial disease (PMD) is a group of complex genetic disorders that arise due to pathogenic variants in nuclear or mitochondrial genomes. Although PMD is one of the most prevalent inborn errors of metabolism, it often exhibits marked phenotypic variation and can therefore be difficult to recognise. Current treatment for PMD revolves around supportive and preventive approaches, with few disease-specific therapies available. However, over the last decade there has been considerable progress in our u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 167 publications
(110 reference statements)
0
37
0
4
Order By: Relevance
“…However, if a beneficial effect deriving from the supplementation of the substrate amino acid is observed in yeast, it is certainly worth to experiment amino acid supplementation in mt ARS -patients. In fact, substrate enhancement, which in some cases can be obtained through dietary supplementation, is an emerging treatment for mitochondrial pathologies [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, if a beneficial effect deriving from the supplementation of the substrate amino acid is observed in yeast, it is certainly worth to experiment amino acid supplementation in mt ARS -patients. In fact, substrate enhancement, which in some cases can be obtained through dietary supplementation, is an emerging treatment for mitochondrial pathologies [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…One additional limitation of our study, also connected to the retrospective nature, is the scarcity of data related to the use of standardized scales to assess the disease course of the movement disorder. Although there are not yet effective disease-modifying therapies, an increasing number of pharmacological clinical trials are being conducted in MDs [ 40 ]. The use of sensitive and valid endpoints is essential to prepare well-stratified clinical cohorts to test the effectiveness of potential treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Most interventions and guidelines are related to symptomatic treatment, with supplementation of cofactors, vitamins, or antioxidants, and mild exercises are recommended. Despite numerous studies, the efficacy of most of these interventions has not been confirmed [ 39 , 40 , 41 , 42 , 43 ].…”
Section: Pharmacological Treatment Of Epilepsy In Patients With Mitochondrial Diseasementioning
confidence: 99%